Low intensity rowing with blood flow restriction over 5 weeks increases V̇O2max in elite rowers: A randomized controlled trial. Issue 3 (March 2020) - Held, Steffen; Behringer, Michael; Donath, Lars
Abstract: Objectives: The present randomized controlled intervention study examined the effects of practical blood flow restriction (pBFR) on maximal oxygen uptake (V̇O2 max) during low intensity rowing. Design: Thirty-one elite rowers were either assigned to the intervention (INT) or control (CON) group, using the minimization method (Strata: Gender, Age, Height, V̇O2 max). Method: While INT (n = 16; 4 female, 12 male, 21.9 ± 3.2 years, 180.4 ± 8.7 cm, 73.6 ± 10.9 kg, V̇O2 max: 63.0 ± 7.9 ml/min/kg) used pBFR during boat- and indoor-rowing training, CON (n = 15, 4 female, 11 male, 21.7 ± 3.7 years, 180.7 ± 8.1 cm, 72.5 ± 12.1 kg, V̇O2 max: 63.2 ± 8.5 ml/min/kg) completed the identical training without pBFR. pBFR of the lower limb was applied via customized elastic wraps. Training took place three times a week over 5 weeks (accumulated net pBFR: 60 min/week; occlusion per session: 2-times 10 min/session) and was used exclusively at low intensities (<2 mmol/L). A spiroergometric ramp test (V̇O2 max; 30–40 W/min increase) on rowing-ergometer and one-repetition maximum test of the squat exercise (SQ1RM) was employed to assess endurance and strength capacity. Results: Significant group × time interactions (ηp ² = 0.26) in favor of INT were found for V̇O2 max (+9.1 ± 6.2%, Effect Size = 1.3) compared to CON (+2.5 ± 6.1%, ES = 0.3). SQ1RM (ηp ² = 0.01) was not affected by the pBFR intervention. Conclusions: This study revealed that 15 sessions of pBFR application with a cumulative total pBFR load of 5 h over a 5 weeks macrocycle remarkably increased V̇O2 max. Thus, pBFR might serve as a promising means to improve aerobic capacity in highly trained elite rowers.